Metode Batik sebagai Upaya Membumikan Budaya Masyarakat Pesisir dalam Pembelajaran Bahasa Indonesia di Pekalongan - Kustriyono, Erwan (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Coastal communities are synonymous with sea and coast, in general, income from seafood and tourism. The education sector becomes a homework for the regional government to develop. Likewise, coastal communities in the city of Pekalongan, they still think the same as coastal communities in general. Then the right method or technique is needed in learning activities. The very basic method that must be introduced to coastal communities is BATIK learning (read, write and work). The BATIK method was introduced in the community, both at universities, high schools and elementary schools. This simple method can foster a literacy culture in the Pekalongan City community which is generally located on the coast of North Coast of Central Java. The Batik Method was introduced in Indonesian language learning in schools and universities. The purpose of this article is to describe the interest in learning of students and students in the Pekalongan City, introducing the BATIK method in learning (especially Indonesian) to students and students in the Pekalongan City. The research method uses the case study method. Data collection techniques using observation, interviews, and documentation. The data analysis method uses the flow model. Data validity test uses triangulation test. The results showed that interest in learning especially Indonesian in Pekalongan City was still low, evidently the interest in reading, writing and making works was still low. The most appropriate and simple solution to arouse interest in learning Indonesian with the BATIK method (read, write and work).